Ectopic Lymphoid Follicles in Multiple Sclerosis: Centers for Disease Control? - Negron, Austin; Stüve, Olaf; Forsthuber, Thomas G. (Frontiers in Neurology, 2020)
Abstract While the contribution of autoreactive CD4+ T cells to the pathogenesis of Multiple Sclerosis (MS) is widely accepted, the advent of B cell-depleting monoclonal antibody (mAb) therapies has shed new light on the complex cellular mechanisms underlying MS pathogenesis. Evidence supports the involvement of B cells in both antibody-dependent and -independent capacities. T cell-dependent B cell responses originate and take shape in germinal centers (GCs), specialized microenvironments that regulate B cell activation and subsequent differentiation into antibody-secreting cells (ASCs) or memory B cells, a process for which CD4+ cells, namely follicular T helper (TFH) cells, are indispensable. ASCs carry out their effector function primarily via secreted Ig but also through the secretion of both pro- and anti-inflammatory cytokines. Memory B cells, in addition to being capable of rapidly differentiating into ASCs, can function as potent antigen-presenting cells (APCs) to cognate memory CD4+ T cells. Aberrant B cell responses are prevented, at least in part, by follicular regulatory T (TFR) cells, which are key suppressors of GC-derived autoreactive B cell responses through the expression of inhibitory receptors and cytokines, such as CTLA-4 and IL-10, respectively. Therefore, GCs represent a critical site of peripheral B cell tolerance, and their dysregulation has been implicated in the pathogenesis of several autoimmune diseases. In MS patients, the presence of GC-like leptomeningeal ectopic lymphoid follicles (eLFs) has prompted their investigation as potential sources of pathogenic B and T cell responses. This hypothesis is supported by elevated levels of CXCL13 and circulating TFH cells in the cerebrospinal fluid (CSF) of MS patients, both of which are required to initiate and maintain GC reactions. Additionally, eLFs in post-mortem MS patient samples are notably devoid of TFR cells. The ability of GCs to generate and perpetuate, but also regulate autoreactive B and T cell responses driving MS pathology makes them an attractive target for therapeutic intervention. In this review, we will summarize the evidence from both humans and animal models supporting B cells as drivers of MS, the role of GC-like eLFs in the pathogenesis of MS, and mechanisms controlling GC-derived autoreactive B cell responses in MS.